2020
DOI: 10.1186/s12909-020-02039-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress coping strategies among medical students and trainees in Saudi Arabia: a qualitative study

Abstract: Background Stress is very common among medical students and trainees. Chronic stress has multiple negative mental and physical health consequences. This study explores medical students and interns’ stressors and their coping strategies. Methods This is a qualitative study involving four focus group discussions with final year medical students (8 males, 10 females) and medical interns (8 males, 7 females). The study was conducted between October 2017 and January 2018 in the premises of a large medical school i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
1
38
1
6
Order By: Relevance
“…Previous studies have reported that medical students used active coping mechanisms (Al-Dubai et al 2011;Chawla and Sachdeva 2018;Gade et al 2014;Abouammoh et al 2020), positive reframing (Al-Dubai et al 2011;Chawla and Sachdeva 2018), planning (Chawla and Sachdeva 2018;Wu et al 2018), positive reappraisal (Wu et al 2018), emotional support (Chawla and Sachdeva 2018;Gade et al 2014), peer discussions (Oku et al 2015) and acceptance (Al-Dubai et al 2011;Chawla and Sachdeva 2018) as means for coping stress. There were minimal reports of usage of avoidance strategies for coping stress among medical students (Al-Dubai et al 2011;Chawla and Sachdeva 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that medical students used active coping mechanisms (Al-Dubai et al 2011;Chawla and Sachdeva 2018;Gade et al 2014;Abouammoh et al 2020), positive reframing (Al-Dubai et al 2011;Chawla and Sachdeva 2018), planning (Chawla and Sachdeva 2018;Wu et al 2018), positive reappraisal (Wu et al 2018), emotional support (Chawla and Sachdeva 2018;Gade et al 2014), peer discussions (Oku et al 2015) and acceptance (Al-Dubai et al 2011;Chawla and Sachdeva 2018) as means for coping stress. There were minimal reports of usage of avoidance strategies for coping stress among medical students (Al-Dubai et al 2011;Chawla and Sachdeva 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nonparametric methods were used as methods of mathematical processing of research results. Since current data on stress coping strategies show that there are gender-related differences in their use [25], the data are described based on respondents' gender. The Mann-Whitney U-test was used to determine differences in the severity of adaptation strategies in self-isolating conditions among male and female representatives.…”
Section: Resultsmentioning
confidence: 99%
“…Women tend to passively submit to external pressure than men. It was previously noted that women use a more emotion-oriented approach and are more likely to use unhelpful (passive) coping strategies than men [47]. It was also found that boys aged 12-19, unlike girls of the same age, recommend that in the case of bullying the offender should be fought back, while girls recommend ignoring the offender [45].…”
Section: Gender Differences In Students' Behavior In a Situation Of Smentioning
confidence: 98%
See 2 more Smart Citations